2018
DOI: 10.3892/ol.2018.9615
|View full text |Cite
|
Sign up to set email alerts
|

Norcantharidin inhibits viability and induces cell cycle arrest and apoptosis in osteosarcoma

Abstract: Osteosarcoma is the most frequent malignant bone tumor in children and adolescents. Norcantharidin (NCTD) is a purified component from blister beetles and has been identified to exert antitumor effects in a variety of cancer types. However, the antitumor effect of NCTD in osteosarcoma remains to be elucidated. In the current study, it was first demonstrated that NCTD inhibited proliferation and induced G2/M-phase arrest and cell apoptosis in human osteosarcoma cells. Furthermore, NCTD significantly decreased t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…NCTD can inhibit the proliferation of osteosarcoma cells by blocking the Akt/mTOR signal transduction pathway and inducing G2/M cell cycle arrest in 143B and SJSA osteosarcoma cells in a dose-and time-dependent manner. At the same time, NCTD led to the upregulation of cleaved caspase-3 and an increase in the downstream target cleaved PARP, which suggested that the extrinsic pathway may also be involved in NCTD-induced cell apoptosis [22]. By evaluating the effects of NCTD on OS cell lines (MG63 and HOS) in vitro and in vivo, we found that NCTD can inhibit cell cycle and induce apoptosis of human OS cells.…”
Section: Introductionmentioning
confidence: 82%
“…NCTD can inhibit the proliferation of osteosarcoma cells by blocking the Akt/mTOR signal transduction pathway and inducing G2/M cell cycle arrest in 143B and SJSA osteosarcoma cells in a dose-and time-dependent manner. At the same time, NCTD led to the upregulation of cleaved caspase-3 and an increase in the downstream target cleaved PARP, which suggested that the extrinsic pathway may also be involved in NCTD-induced cell apoptosis [22]. By evaluating the effects of NCTD on OS cell lines (MG63 and HOS) in vitro and in vivo, we found that NCTD can inhibit cell cycle and induce apoptosis of human OS cells.…”
Section: Introductionmentioning
confidence: 82%
“…In addition, we identified seven TCM drugs that target CYP2E1. Recent research has provided evidence that natural active ingredients in TCM drugs have practical antitumor therapeutic effects on solid tumors 42 . Network pharmacology has been extensively applied by researchers 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has provided evidence that natural active ingredients in TCM drugs have practical antitumor therapeutic effects on solid tumors. 42 Network pharmacology has been extensively applied by researchers. 43 18beta‐glycyrrhetinic acid, styrene, toluene, nicotine, m‐xylene, p‐xylene, and colchicine may play a role in gliomas by influencing CYP2E1, which requires further study.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that NCTD 24 and PTX 25 induced cell cycle arrest in multiple cancer cells. Moreover, this study next clarified whether NCTD combined with PTX induces cell cycle arrest.…”
Section: Resultsmentioning
confidence: 97%